Dakwah dan Peran Pembelajaran Bahasa Arab dalam Perubahan Sosial - ikhwan, Nur; ., Burhanuddin (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This paper explores the relationship between Da'wah (Islamic propagation) and the role of Arabic language learning in facilitating social change. Da'wah is a fundamental aspect of Islam, aiming to spread the message of the religion and bring about positive transformations in society. Arabic language, as the language of the Qur'an and the primary medium for Islamic teachings, plays a crucial role in the practice of Da'wah. This study investigates how the acquisition of Arabic language skills can empower individuals to effectively engage in Da'wah activities and contribute to social change. It examines the impact of Arabic language learning on enhancing communication, understanding, and interpretation of Islamic teachings, as well as fostering cultural appreciation and interfaith dialogue. The paper also discusses the challenges and opportunities associated with Arabic language learning in the context of Da'wah, including the availability of resources, pedagogical approaches, and the role of technology. The findings highlight the significance of Arabic language learning as a catalyst for social change through Da'wah, emphasizing the need for comprehensive language education programs that incorporate both linguistic and religious components.